Project-Based Learning through the STEM Approach in Elementary Schools: How to Improve Problem-Solving Ability - Abdur Rasyid; Rinto Rinto; Mulia Susanti (Papanda Publisher, 2023)
Problem-solving ability is a fundamental competence that must be mastered by students. Consequently, the educational orientation across various stages of learning should emphasize the development of this competence. The objective of this study is to enhance problem-solving skills among sixth-grade students at SDN Munjul 03 through the implementation of Project-Based Learning model with a STEM (Science, Technology, Engineering, and Mathematics) approach. The research approach employed is quantitative, employing a pre-experimental design with a one-group pretest-posttest design. The research sample comprises 41 sixth-grade students at SDN Munjul 03. Data for this study were collected through observation, interviews, and tests. The findings of the research reveal that the average scores in the problem-solving skills test after the implementation of the Project-Based Learning model with the STEM approach are significantly better than before. Descriptive analysis of these results indicates a notable enhancement in problem-solving skills among students following the Project-Based Learning treatment with a STEM approach. The results of the hypothesis testing, utilizing the paired sample t-test method, also indicate that the difference between pre-treatment and post-treatment problem-solving skills test scores is statistically significant. Consequently, it can be deduced that a tangible improvement has occurred in the problem-solving abilities among the experimental class students. The conclusion drawn from this study is that the Project-Based Learning model with a STEM approach is effective in elevating problem-solving skills. The implementation of the Project-Based Learning model through the STEM approach can be regarded as one of the alternative solutions available to educators for enhancing students' problem-solving capabilities.